2012
DOI: 10.1111/j.1468-5906.2012.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Trust in a “Fallen World”: The Case of Protestant Theological Conservatism

Abstract: Important questions remain about religion-based variations in the propensity to trust. A new perspective on the religion-trust nexus is proposed by examining Protestant theological conservatism as a moral framework reflected in personal convictions about scripture (the authoritativeness of the Bible), sin (beliefs in human depravity and the existence of hell), and salvation (the need for a born-again experience to be saved). Findings indicate that personal commitment to this framework is negatively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 72 publications
1
58
1
Order By: Relevance
“…Indeed, some have claimed that churches can use politics to compete for adherents in the religious marketplace (Audette and Weaver ). On the other hand, churches may choose to direct these skills toward salvific practices—presumably, the primary goal of churches—and less on political or community action (Dingemans and Van Ingren ; Hempel and Bartkowski ; Hempel, Matthews, and Bartkowski ). If true, it suggests, unlike evidence form the U.S. context, that increased participation in church activities may be responsible for decreased participation due to an increased focus on theological or spiritual development.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some have claimed that churches can use politics to compete for adherents in the religious marketplace (Audette and Weaver ). On the other hand, churches may choose to direct these skills toward salvific practices—presumably, the primary goal of churches—and less on political or community action (Dingemans and Van Ingren ; Hempel and Bartkowski ; Hempel, Matthews, and Bartkowski ). If true, it suggests, unlike evidence form the U.S. context, that increased participation in church activities may be responsible for decreased participation due to an increased focus on theological or spiritual development.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals who believe the Bible should be taken literally, word for word, are less likely than non-literalists to give of their time, skills, and money to organizations outside the congregation. As Hempel et al (2012) demonstrate, theological conservatism is negatively related to the propensity to trust ''unknown others''. Our findings dovetail with theirs and are consistent with the idea that people committed to a particular strand of theological conservatism are less likely to engage in broader civic life, likely due to lower levels of generalized trust (Hempel et al, 2012).…”
Section: Congregation-level Small Groupsmentioning
confidence: 90%
“…If religiosity is related to solidarity principles, then why would religious belief be detrimental? An answer may come from previous studies finding that religious groups with liberal convictions showed more pro‐social attitudes and behavior than religious groups with conservative convictions (Hempel, Matthews, and Bartkowski ; Lam ; Wilson and Janoski ). Apparently, there are elements in conservative religious convictions and values that counterbalance (or in some cases even outweigh) positive elements such as caring about fellow human beings.…”
Section: Discussionmentioning
confidence: 99%
“…() argued that theological precepts cause differences in the extent to which people trust strangers. Because the doctrine of mainline Protestant denominations focuses on horizontal relationships (the “priesthood of all believers”) (Hempel, Matthews, and Bartkowski :525), some authors suggest that they should be able to extend their trust in others across the borders of their own community (thereby enhancing their generalized trust). In contrast, Banfield () argues that Catholics have lower levels of social trust compared to Protestants because of “amoral familism,” or a tendency to be socially oriented toward family and close friends, which may restrict their perceived moral community and thus their generalized trust (Traunmüller ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%